Clinicopathological features and genetic mutation spectrum of primary anastomosing hemangioma arising from the kidney - Zhang, Luxin; Li, Haozhen; Tong, Heyao; Cui, Hepeng; Guo, Huahang; Wen, Shuang; Song, Zhuwei; Chen, Jiaqiang; Xiang, Shengxiang; Liu, Zhiyu; Fan, Bo; Wang, Liang (Frontiers in Immunology, 2025)
BackgroundRenal anastomosing hemangioma (RAH) is a rare benign renal tumor, and its clinicopathologic characteristics and genetic mutation spectrum related to its mechanisms of pathogenesis are unclear.MethodsWe carried out whole-genome sequencing (WGS) on RAH samples to explore the genetic mutation spectrum and verified the results by Sanger sequencing. Immunohistochemical analysis was also performed to reveal the histopathological characteristics and the tumor microenvironment components. Moreover, a population-based study was conducted after searching the PubMed, EMBASE, and Ovid SP databases to systematically summarize the clinicopathologic features of patients with RAH.ResultsWGS analysis revealed 10532 somatic single-nucleotide variants (SNVs), 6705 somatic insertions and deletions (INDELs), and mutations in 32 predisposing genes and 10 driver genes, among which the mutations in 8 of the predisposing genes, CNTNAP2, NCOA2, FAT1, MET, TJP2, MAML2, SRGAP3, and CSMD3, and the mutation site in the driver gene HIP1 were confirmed by Sanger sequencing. Moreover, the immunohistochemical profile of the tumor microenvironment revealed that the expression content of tumor-associated macrophages (CD163, CD68) and fibroblasts (SMA) differs between cancerous and precancerous tissues which may regulate the disease development. On the basis of our population-based analysis, we summarized the clinicopathological features of 100 patients with RAH and identified significant differences in age (p=0.001), tumor site (p<0.001), tumor focality (p<0.001), largest tumor diameter (p=0.001) and surgical approach (p=0.010) between patients with RAH with end-stage renal disease (ESRD) and those without ESRD.ConclusionsThe distinct phenotypes of RAH may be associated with the different genetic mutation spectra identified in our study. The presence or absence of comorbid ESRD varies among patients with RAH. However, additional studies are required to validate our results.